INVESTIGATING THE EFFECT OF CUSTOMER RELATIONS QUALITY AND PRODUCT EXCELLENCE ON MARKETING PERFORMANCE THROUGH PRODUCT COMPETITIVE ADVANTAGE (Empirical Study at PT Bank Mega, Tbk) - Augustia, Sekarani Yuteva; Raharjo, Susilo Toto; Sutopo, Sutopo (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2018)
In this highly competitive banking industry, every bank needs to create superior value for its customers. The ideal banking industry to improve the quality of customer relationships is a company that wants to optimize profits by closer (customer intimacy) and harmonious relationship with its customers. Thus, the value-added relationship marketing can be optimized in streamlining and streamlining costs to acquire new customers or retain old customers so that the cost and marketing efforts are not in vain and profits can be increased even more. This study specifically examines the effect of customer relationship quality and product excellence on the company's marketing performance through a competitive advantage in the banking industry. The industry that is used as a research object is PT Bank Mega, Tbk Regional Semarang. The analytical tool used in this study is the Structural Equation Model (SEM) of the AMOS statistical package. From the research results can be concluded that the quality of relationships influence and positive product superiority to marketing performance. While a competitive advantage does not have a positive effect on marketing performance. At the end of the discussion, the limitations of research and future research agenda can be used as a reference for further study or research.